2022
DOI: 10.3389/fphar.2022.878556
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Geranylgeraniol in Managing Bisphosphonate-Related Osteonecrosis of the Jaw

Abstract: Medication-related osteonecrosis of the jaw (ONJ) is a rare but significant adverse side effect of antiresorptive drugs. Bisphosphonate-related ONJ (BRONJ) is the most prevalent condition due to the extensive use of the drug in cancer and osteoporosis treatment. Nitrogen-containing bisphosphonates suppress osteoclastic resorption by inhibiting farnesyl pyrophosphate synthase in the mevalonate pathway, leading to deficiency of the substrate for GTPase prenylation. The bone remodelling process is uncoupled, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 75 publications
2
12
0
1
Order By: Relevance
“…These effects have been attributed to the inhibition of farnesyl pyrophosphate (FPP) synthase, GGPP synthase, or both [42]. It has been previously shown that the induction of cell apoptosis is produced due to the formation of ATP analogues by suppressing the mevalonate pathway [43]. In the present study, zoledronate did not exert this detrimental effect on the osteoblasts grown on GG-M (p < 0.001) (Figure 1).…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…These effects have been attributed to the inhibition of farnesyl pyrophosphate (FPP) synthase, GGPP synthase, or both [42]. It has been previously shown that the induction of cell apoptosis is produced due to the formation of ATP analogues by suppressing the mevalonate pathway [43]. In the present study, zoledronate did not exert this detrimental effect on the osteoblasts grown on GG-M (p < 0.001) (Figure 1).…”
Section: Discussionsupporting
confidence: 42%
“…It seems that GGOH can even rescue cells from the apoptotic effects of nitrogen-containing BPs. GGOH inhibits caspase-3 activation, and thus apoptosis, by inhibiting geranylgeranyl transferase I through an increase in the amount of substrate available for GTPase prenylation [43]. It has also been described that at low doses, GGOH (10-40 µM) may promote osteoblasts' viability [25,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the polyprenol salvage pathway was first observed more than 25 years ago, but the enzymes responsible in animals or any pathogen are still unident ified [72,80]. Despite this, the interest in this pathway for the treatment of several human pathologies, ranging from osteonecrosis to infectious diseases, is increasing [92,93]. As a consequence, it is impractical to mention here everything published in this field, and we needed to make a selection of those reports that best illustrated the topics discussed, with a focus on biomedical problems.…”
Section: Biomedical Importance Of the Geranylgeraniol And Farnesol Sa...mentioning
confidence: 99%